The gods of the city : Protestantism and religious culture in Strasbourg, 1870-1914 - Steinhoff, Anthony J. (Studies in Central European histories ;, 2008)
Drawing on extensive archival research, this study of Protestantism in Strasbourg (1870-1914) rethinks traditional understandings of the relationship between religion and European urban modernity.